Finansowanie inwestycji poprzez emisję obligacji przychodowych - doświadczenia amerykańskie a rynek polski - Wojtasiak, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Revenue bonds are issued for enterprise financing that are secured by the revenues generated by the completed projects themselves. The paper presents revenue bonds classification according the type of financing. These include utility revenue bonds, transportation revenue bonds, housing revenue bonds, higher education revenue bonds, health care revenue bonds, industrial development revenue bonds. As a model American bonds market is used. Attention is paid as well on the Polish revenue bonds market, which is in the early stage of development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 517-524